2008
DOI: 10.1021/la800174n
|View full text |Cite
|
Sign up to set email alerts
|

Liposome Modified with Mn−Porphyrin Complex Can Simultaneously Induce Antioxidative Enzyme-like Activity of Both Superoxide Dismutase and Peroxidase

Abstract: An antioxidative liposome catalysis that mimics both superoxide dismutase (SOD) and peroxidase (POD) activities has been developed by using the liposomes modified with lipophilic Mn-(5,10,15,20-tetrakis[1-hexadecylpyridium-4-yl]-21H,23H-porphyrin) (Mn-HPyP). The SOD- and POD-like activities of the Mn-HPyP-modified liposome were first investigated by varying the type of phospholipid, such as 1,2-distearyl-sn-glycero-3-phosphocholine (DSPC), 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC), 1,2-dipalmitoyl-sn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…"raft" domains) in cells has attracted much attention because of its implications for membrane-related processes, including bacterial and viral infections and signal transductions [22]. Recent studies have also revealed that the lipid membranes can activate the biomacromolecules and regulate their functions [6][7][8][9][39][40]. Liposomes have been intensely studied as a biomimetic environment of lipid bilayers.…”
Section: "Liposome Membrane Design" For Recognition Of Biomacromoleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…"raft" domains) in cells has attracted much attention because of its implications for membrane-related processes, including bacterial and viral infections and signal transductions [22]. Recent studies have also revealed that the lipid membranes can activate the biomacromolecules and regulate their functions [6][7][8][9][39][40]. Liposomes have been intensely studied as a biomimetic environment of lipid bilayers.…”
Section: "Liposome Membrane Design" For Recognition Of Biomacromoleculesmentioning
confidence: 99%
“…A liposome membrane is effective in its use as a platform to perform the above purpose because it looks after the fundamental characteristics of a conventional extraction system and the recognition surface of the biomolecule ( Figure 1). In practice, there are many reports on the possible role of a liposome membrane to recognize various molecules , such as asymmetric recognition [56-57], metal affinity [4], peptide recognition [7,58], enzyme-like function [8,59], RNA recognition [6,42,48], and others [9,28] (Figure 8). membrane modules [61], and hydrogel immobilization of the liposomes at high concentration ( Figure 9) [62].…”
Section: Conclusion and Future Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…1(b), the membrane fluidity was reduced in correspondence with the decrease of the SOD activity. It has been reported that the phase transition temperature of the POPC, DMPC, and DPPC liposomes are -4 ℃, 23 ℃, and 45 ℃, respectively 27) , where the POPC liposomes exists in a liquid crystalline phase at the temperature tested here. It has also reported that the membrane fluidity of the liposome could increase the hydrophobicity of the liposome surface 28, 29) .…”
Section: Activity and Adsorption Of Oxidized Andmentioning
confidence: 99%
“…On the other hand, the antioxidative activity 4 ~ 6) or gene expression system 3) have been well constructed on liposome membrane, which is called as LIPOzyme (liposome + enzyme). The previous reports on the LIPOzyme have indicated that the lipid composition and the phase state of lipid membrane, such as liquid-ordered (lo) phase, liquid-disordered (ld) phase and their mixture (ld + lo) phase, could control their function 5) . Therefore, a systematic investigation on the membrane properties as a function of the lipid composition is expected to contribute to the understanding not only on the phenomena in cell system but also on the effective design of novel biomaterials such as LIPOzyme.…”
Section: Introductionmentioning
confidence: 99%